Quantification of the overall measurement uncertainty associated with the passive moss biomonitoring technique: Sample collection and processing. (May 2017) - Aboal, J.R.; Boquete, M.T.; Carballeira, A.; Casanova, A.; Debén, S.; Fernández, J.A.
Abstract: In this study we examined 6080 data gathered by our research group during more than 20 years of research on the moss biomonitoring technique, in order to quantify the variability generated by different aspects of the protocol and to calculate the overall measurement uncertainty associated with the technique. The median variance of the concentrations of different pollutants measured in moss tissues attributed to the different methodological aspects was high, reaching values of 2851 (ng·g −1 ) 2 for Cd (sample treatment), 35.1 (μg·g −1 ) 2 for Cu (sample treatment), 861.7 (ng·g −1 ) 2 and for Hg (material selection). These variances correspond to standard deviations that constitute 67, 126 and 59% the regional background levels of these elements in the study region. The overall measurement uncertainty associated with the worst experimental protocol (5 subsamples, refrigerated, washed, 5 × 5 m size of the sampling area and once a year sampling) was between 2 and 6 times higher than that associated with the optimal protocol (30 subsamples, dried, unwashed, 20 × 20 m size of the sampling area and once a week sampling), and between 1.5 and 7 times higher than that associated with the standardized protocol (30 subsamples and once a year sampling). The overall measurement uncertainty associated with the standardized protocol could generate variations of between 14 and 47% in the regional background levels of Cd, Cu, Hg, Pb and Zn in the study area and much higher levels of variation in polluted sampling sites. We demonstrated that although the overall measurement uncertainty of the technique is still high, it can be reduced by using already well defined aspects of the protocol. Further standardization of the protocol together with application of the information on the overall measurement uncertainty would improve the reliability and comparability of the results of different biomonitoring studies, thus extending use of the technique beyond the context of scientific research. Graphical abstract: Highlights: The overall measurement uncertainty associated with the moss technique was calculated. Uncertainty decreased when using the worst vs. standardized vs. optimal experimental set up. Although the overall uncertainty of the technique is still high, it can be reduced. Standardization of the protocol improves the reliability and comparability of the results. Abstract : Measurement uncertainty associated to the results of the moss technique is significantly reduced when applying a standardized protocol.